Visual Chaos of the Formal Order of the University Buildings - Zainab Ibrahim Abbas (المجلة العراقية لهندسة العمارة والتخطيط, 2018)
This Paper Studies Visual Chaos phenomenon in the University of Technology, after the development and rehabilitation of its Buildings, Which was the reason for the absence of the formal order Unity of its Buildings. So the aim of this paper is to built a base Knowledge to visual chaos phenomenon, Order and Formal Order. The research hypothesis was “there is a visual chaos in the formal order of the elevations and the master plan of the University of Technology”. The research defines the visual chaos as the absence of order in the formal pattern. The research has built a theoretical framework defined the visual chaos, and project it, on a selected buildings that have been rehabilitated and a new project of the University of Technology. The main research findings was the absence of identity of the final product elevations, and the master plan of the University, which was the reason for the visual chaos of the formal order. The absence of planning and good design for the master plan and elevations was the reason for ignoring the unity in the form and context. So the paper insist on finding a relation between old and new through investing elements and formal properties which create